Strategi Pengembangan Manajemen Perguruan Tinggi Swasta - Sonedi Sonedi (Anterior Jurnal, 2018)
Higher education is the level of education after the secondary education that includes diploma programs, undergraduate programs, master programs, doctoral programs, and professional programs, as well as special programs, organized by universities based on Indonesian culture. One of the common characteristics of organizational development is that organizational development is a continuous and dynamic process. Executors should be able to change strategy during the ongoing process as a result of emerging problems and organizational events. This is because it has a strong influence on the achievement of college goals, especially organizational development concerning financial perspective, costumer, education service process, and learning and growth. Balanced Scorecard (BSC) as an alternative to organizational development. Within the framework of organizational development, PTS should optimize education services with the potential of existing resources in accordance with the demands of the internal and external environment.